Is there Cointegration between Renewable Energy and Economic Growth in Selected Sub-saharan African Counries? - Alege, Philip; Jolaade, Ayobami; Adu, Omobola (International Journal of Energy Economics and Policy, 2018)
Globally, much attention is being paid to the environment due to the negative effects of environmental degradation on human lives resulting from population growth for instance. With a growing population in Africa it is only natural that the demand for energy for various activities would continue to grow. At present, most of the energy being produced and consumed in Sub-Saharan Africa is derived from non-renewable sources which have triggered calls to shift attention to renewable energy sources. This situation raises some pertinent research questions. Is there a relationship between renewable energy and economic growth in some selected sub-Saharan African countries? Through a panel co-integration approach, the findings revealed that there is a long-run relationship between renewable energy and economic growth in the selected Sub-Saharan African countries. This calls for the implementation of public policies towards the promotion of renewable energies in Africa to combat the negative effects of carbon emissions. Keywords: Renewable energy, Economic growth, Panel data, Co-integration, Sub-Saharan Africa JEL Classifications: K32, P18, Q28